The paradigm of locational competition - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
Locational competition is geographic competition, competition between places, between cities, between regions, and between countries. These spatial units compete with each other for the mobile production factors in factor markets, i.e., for mobile capital, for mobile technical know-how, and for mobile highly qualified labor. Countries compete with their taxes, their infrastructure and their institutional setups. Mobile capital can leave a country when conditions there become unfavorable, for example, when taxes are raised. Taxation drives capital out of the country, whereas infrastructure attracts capital. Obviously, there is a trade-off between these two effects. In addition to tax competition and competition in providing public goods (infrastructure competition), there is also competition between institutional rules, i.e., between product standards, permitting procedures, or other legal regulations (institutional competition). The exit option of capital redefines the opportunity costs of taking economic policy measures and thus also redefines policymakers' cost-benefit calculus. Policymakers' decision-making scope is reduced because the tax base in a country shrinks when real capital emigrates. In addition, when real capital emigrates, labor productivity drops, which reduces income and job opportunities and diminishes the tax base. Locational competition impacts heavily on the position of unions because expansionary wage policies, i.e., increases in wage rates that go beyond employment-neutral productivity increases, cause capital to emigrate. This amplifies the effect of such policies on employment. As a result unions' power wanes, which can be seen in the drop in membership. The fear that there will be an unlimited race to the bottom is unfounded. There are numerous ways, even given international competition, of ensuring that infrastructure is provided without causing capital to emigrate. The discussion about the race to the bottom has obscured the fact that locational competition, like product competition, is a discovery process in the sense of Hayek, a means of reducing costs and finding new solutions. This is why the institutional competition in the EU, which was brought about by the Cassis de Dijon verdict of the European Court of Justice when establishing the country-of-origin ruling, has become a national regulations can opener. Locational competition puts interest groups under pressure, thus constraining rentseeking. It also tames governments. Locational competition will have its impact on national economic policies. Governments will be forced to look at international benchmarks for their own policies. This holds for stabilization policy, for tax policy, for infrastructure policy, and it also begins to apply to social policy. Economic policies undertaken by the major European governments can be explained with the concept of locational competition.
Keywords: 330; Standortwettbewerb; Institutioneller Wettbewerb; Internationaler Wettbewerb; Standortpolitik; Wirtschaftsreform; Theorie; Deutschland